Prime Minister Decree No. 1257/2014 On Increasing the Sale Price of the Electric Energy = قرار رئيس مجلس الوزراء رقم 1257 لسنة 2014 بشأن زيادة أسعار بيع الطاقة الكهربائية / Prime Minister. - Egypt. Prime Minister (2025)
Prime Minister Decree no. 1257/2014 on increasing the sale price of the electric energy قرار رئيس مجلس الوزراء رقم 1257 لسنة 2014 بشأن زيادة أسعار بيع الطاقة الكهربائية